Morphometric Characteristic and Distribution of Hummocky Hills in Debris Avalanche Deposit of Galunggung Volcano, West Java, Indonesia - Alfin, A. S. (2022)
Sector collapse of a volcanic body produces topography of horseshoe-shaped caldera incisions and a widespread hummocky hill resembling debris avalanche deposit. The study of morphometry, distribution, and the alignment of the hummocky hills is necessary to understand the source and deposition process of the debris-avalanche deposit. Galunggung volcano is, one of the volcanoes in Java Island, attributed with 7 km wide of caldera opens towards the east direction (N 135° E) where hummocky hills cover an area of ∼32 km2. Morphometry of the hummocky hills is 500-700,000 m2 in size, elongation ratio of 1.3-3.9. Hummocky hills are distributed 0.5 to 20 km distance from the summit of the Galunggung volcano. The elongation orientation of the hummocky hills is deviated from the main flow direction forming various angles. We divide the deviation angle into parallel (0-45°) and perpendicular orientation (45-90°). The maximum size of the hummocky hills generally decreases towards increasing distance from the summit. These hills also show changes in alignment from perpendicular to parallel, suggesting a typical free flow pattern of debris-avalanche deposits. © Published under licence by IOP Publishing Ltd.